Nipple-Sparing Mastectomy and Immediate Reconstruction: A Propensity Score–Matched Analysis of Satisfaction and Quality of Life. Issue 6 (15th September 2022) - Kokosis, George; Stern, Carrie S.; Shamsunder, Meghana G.; Polanco, Thais O.; Patel, Vaidehi M.; Slutsky, Hanna; Morrow, Monica; Moo, Tracy-Ann; Sacchini, Virgilio; Coriddi, Michelle R.; Cordeiro, Peter G.; Matros, Evan; et al.
Abstract : Background: Although it is intuitive that nipple-sparing mastectomy in selected patients would result in excellent cosmetic outcomes and high patient satisfaction, studies of clinical outcomes and health-related quality of life are limited and show mixed results. This study aimed to use a propensity score–matching analysis to compare satisfaction and health-related quality-of-life outcomes in patients who underwent implant-based reconstruction following bilateral nipple-sparing mastectomy or skin-sparing mastectomy. Methods: A propensity score–matching analysis (1:1 matching, no replacement) was performed comparing patients undergoing nipple-sparing or skin-sparing mastectomy with immediate bilateral implant-based breast reconstruction. Patients with a history of any radiation therapy were excluded. Matched covariates included age, body mass index, race, smoking history, neoadjuvant chemotherapy, bra size, and history of psychiatric diagnosis. Outcomes of interest included BREAST-Q scores and complications. Results: The authors examined 1371 patients for matching and included 460 patients (nipple-sparing mastectomy, n = 230; skin-sparing mastectomy, n = 230) in the final analyses. The authors found no significant differences in baseline, cancer, and surgical characteristics between matched nipple-sparing and skin-sparing mastectomy patients, who also had similar profiles for surgical complications. Interestingly, the authors found that postoperative Satisfaction with Breasts scores and all other health-related quality-of-life domains were stable over a 3-year period and did not differ significantly between the two groups. Conclusions: Compared with skin-sparing mastectomy, bilateral nipple-sparing mastectomy did not improve patient-reported or clinical outcomes when combined with immediate implant-based reconstruction. The impact that nipple-sparing mastectomy may have on breast aesthetics and the ability of the BREAST-Q to gauge an aesthetic result following nipple-sparing mastectomy warrant further investigation. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.